International Legal Protection of Genetic Resources Against Biotechnological Piracy - Tounsi, Sabrina (Journal of Legal Studies and Researches, 2026)
The various applications of biotechnology depend on genetic resources, whether they are plants, animals or microorganisms. The close interdependence between biotechnology and genetic resources is clear, as genetic resources are used to improve agricultural varieties and develop biotechnological industry products, such as foodstuffs and pharmaceuticals, while providing biotechnology solutions to agricultural, medical and industrial problems. Genetic resource piracy occurs when a country's vital resources are seized without permission or acknowledgement of ownership, allowing them to be used to establish global economies. To confront biopiracy, we must respect the sovereignty of countries over their wealth and recognise the genetic resources of developing countries.